2015
DOI: 10.1016/j.ceramint.2014.12.104
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally synthesized BaTiO3 textured in a strong magnetic field

Abstract: Hydrothermally synthesized BaTiO 3 was colloidally consolidated by slip casting and by electrophoretic deposition in a high strength magnetic field of 17.4 T. Textured BaTiO 3 was successfully prepared by both processing techniques, with the {001} plane aligning normal to the direction of the magnetic field. The initial alignment in the green powder compact was preserved and enhanced after sintering from 1400 1C to 1500 1C. The sintering temperature hardly influenced the degree of texture in slip cast samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Here, it was observed that sintering at 1500°C can improve texture of . Vriami et al [4] also reported an improvement of the orientation factor for (prepared by the same synthesis route as described in 2.1 and 2.2) aligned by electrophoretic deposition in a 17.4 vertical magnet and sintered at 1500°C. The slip casted sample showed a maximum in the orientation factor at 1450°C and a mild decrease at 1500°C.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Here, it was observed that sintering at 1500°C can improve texture of . Vriami et al [4] also reported an improvement of the orientation factor for (prepared by the same synthesis route as described in 2.1 and 2.2) aligned by electrophoretic deposition in a 17.4 vertical magnet and sintered at 1500°C. The slip casted sample showed a maximum in the orientation factor at 1450°C and a mild decrease at 1500°C.…”
Section: Resultsmentioning
confidence: 89%
“…Texturing of ceramic materials by colloidal processing is one of these techniques. Colloidal processing has been extensively investigated for net shaping methods such as gel casting [1][2][3], electrophoretic deposition [4,5] and slip casting [4,[6][7][8][9]. Controlled conditions of the starting powder, slurry preparation, organic additive removal and sintering resulted in high-quality dense ceramic materials for industrial, medical and commercial use.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the transmittance measurement, we know that the LiNbO 3 ferroelectric nanocrystals align after poling, while the preferential orientation of LiNbO 3 nanocrystals is not very clear. For ferroelectric nanocrystals/polymer system, the nanocrystals will be aligned to the most stable state with lowest energy under external electric field [17]. For LiNbO 3 nanocrystals, the spontaneous polarization pointing is along [001] direction, which means it's the most susceptible direction under external electric field [18].…”
Section: Resultsmentioning
confidence: 99%